2014 : the election that changed India - Sardesai, Rajdeep (Penguin Books, 2015)
"The 2014 Indian general elections has been regarded as the most important elections in Indian history since 1977. It saw the decimation of the ruling Congress party, a spectacular victory for the BJP and a new style of campaigning that broke every rule in the political game. But how and why? In his riveting book, Rajdeep Sardesai tracks the story of this pivotal elections through all the key players and the big news stories. Beginning with 2012, when Narendra Modi won the state elections in Gujarat for a third time but set his sights on a bigger prize, to the scandals that crippled Manmohan Singh and UPA 2 and moving to the back-room strategies of Team Modi, the extraordinary missteps of Rahul Gandhi and the political dramas of an election year, he draws a panoramic picture of the year that changed India."--Publisher's information.